2020
DOI: 10.18231/2393-9087.2018.0029
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer potentials of the plant Aquilaria malaccensis leaves

Abstract: In the present study the ethanolic extract of Aquilaria malaccensis (Agar wood) leaves before inoculation (BF) and after inoculation (AF)) was evaluated for its anticancer potentials. The leaf extracts (BF and AF) was subjected to in-vitro cytotoxicity studies on EAC cells, normal spleen cells and DLA cells. The leaf extracts showed dose dependent cytotoxicity with increase in dose. The IC50 value for BF and the AF leaf extract was 79.09μg/ml and 79.20μg/ml respectively. The effect on primary spleen cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Aquilaria malaccensis, belonging to the Thymelaeaceae family, was found to be cytotoxic against DLA and EAC cancer cells (IC 50 values were 72 and 79 µg/mL, respectively). However, the cytotoxicity against normal cells was negligible [129]. Another study evaluated the cytotoxicity of the oil fraction of the plant extract against HCT116 colon cancer cells and reported an IC 50 value 4 µg/mL [130].…”
Section: Thymelaeaceaementioning
confidence: 99%
“…Aquilaria malaccensis, belonging to the Thymelaeaceae family, was found to be cytotoxic against DLA and EAC cancer cells (IC 50 values were 72 and 79 µg/mL, respectively). However, the cytotoxicity against normal cells was negligible [129]. Another study evaluated the cytotoxicity of the oil fraction of the plant extract against HCT116 colon cancer cells and reported an IC 50 value 4 µg/mL [130].…”
Section: Thymelaeaceaementioning
confidence: 99%
“…Aquilaria malaccensis leaves extract has antioxidant (Hendra et al, 2016;Halim et al, 2022), antiviral against dengue virus (Masita et al, 2020) and immunomodulatory potential (Batubara et al, 2021;Wahid et al, 2022;Yana et al, 2022). Furthermore, the stem has been referenced for anticancer activities (Hegde et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A phytochemical finding also revealed the presence of flavonoid glycosides, 2-(2-phenylethyl) chromenes, lignans and diterpenoids in this plant extract ( Musa et al 2019 ). Numerous studies have been performed to examine the possible use of the extracts in diabetes care, arthritis, infection, inflammation, oxidation stress and cancer ( Zulkifle et al 2018 ; Hegde et al 2018 ; Mokhtar et al 2021 ). Previous studies of agarwood also reported the capability of Aquilaria species to demonstrate laxative and antidepressant effects in humans ( Kakino et al 2010 ; Wang et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%